2016
DOI: 10.1017/s0261444815000452
|View full text |Cite
|
Sign up to set email alerts
|

International teaching assistants at universities: A research agenda

Abstract: International teaching assistants (ITAs) are Indian, Chinese, Korean, Turkish, etc. international students who have been admitted to graduate study at universities in the U.S.A. and Canada, and are being supported as instructors of undergraduate-level classes and labs in biology, chemistry, physics, and math. For the past 30 years, the number of ITAs has been increasing, and many departments at universities have come to rely largely on ITAs to cover their undergraduate teaching needs. As high-intermediate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…These unexpected changes to UNCU's semester due to COVID-19 likely played a significant role in the responses of the post-survey data. Nonetheless, in answering the research sub-question regarding ITAs' self-perceptions in areas commonly identified as being of concern in previous literature (Li et al, 2011;Gorsuch, 2016;Smith and Khawaja, 2011;Sherry et al, 2010), a preliminary statistical review yields interesting findings to be used for indicative purposes only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These unexpected changes to UNCU's semester due to COVID-19 likely played a significant role in the responses of the post-survey data. Nonetheless, in answering the research sub-question regarding ITAs' self-perceptions in areas commonly identified as being of concern in previous literature (Li et al, 2011;Gorsuch, 2016;Smith and Khawaja, 2011;Sherry et al, 2010), a preliminary statistical review yields interesting findings to be used for indicative purposes only.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, various studies outline American undergraduates' negative attitudes toward ITAs. They are often viewed as having linguistic inadequacies (Li et al, 2011;Gorsuch, 2016) and receive lower student evaluations compared to American TAs (Manohar and Appiah, 2015). Work by Meyer and Mao (2015) demonstrates that American students also perceive ITAs as creating classroom environments that are less desirable than those developed by American TAs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case study with a Chinese biology international teaching assistant (ITA) who was engaged in a team-teaching practicum with a native speaker TA in an undergraduate lab, Gorsuch (2005) found that the ITA engaged in self-vocalization and self-repair while lecturing on content, and during interactions with undergraduates and argued for a broader application of the Output Hypothesis beyond learners' immediate responses to interlocutors' non-comprehension in that the act of teaching might … push ITAs into communicating their ideas with greater than ordinary care in order to be comprehensible (Gorsuch, 2016).…”
Section: Output Hypothesismentioning
confidence: 99%
“…Therefore, the output hypothesis states that "language production is necessary because it forces learners to move beyond semantic processing of language during comprehension and focuses their attention toward syntactic use of language" (Kim, 2017, p. 127), as well as making themselves more comprehensible to their interlocutors as observed in Gorsuch (2016). Thus, output tasks and opportunities should be given and the learners need to be pushed to use the L2 in a productive mode, for example, speaking (Wen, 2018).…”
Section: Output Hypothesismentioning
confidence: 99%